Implementación de un sistema hidráulico de tuberías en serie y paralelo para determinar caídas de presión debidas a perdidas en tuberías y aditamentos (2023)
This work has as main objective to establish the pressure drops in pipes and accessories of hydraulic networks through a test bench. The variation of the geometries of the pipes and accessories, as well as the instrumentation for the measurement will be made; In order to better calculate and anticipate the behavior of liquids such as water for these tests, the material from which the pipes will be made, the diameter of the control valves and the accessories will be taken into account.